Asthma prevention and recent advances in management - Doina Anca Pleșca; Marcela Ionescu; Anca Cristina Dragănescu (Elsevier, 2024)
Asthma is the most frequent chronic disease of childhood, affecting up to 20 % of children worldwide. The authors present the current literature focusing on primary and secondary prevention of both early and late childhood asthma and the recent advances in management. The therapeutic tools for pediatric asthma have expanded significantly for both the non-severe and severe forms. The use of anti-inflammatory treatment, even for the mildest cases, and the withdrawal of symptomatic bronchodilation as monotherapy have been included in the most recent guidelines. The different biological therapies have revolutionized the therapeutical approach for severe uncontrolled asthma in children and adolescents.The main guidelines on asthma maintenance therapy in pediatrics suggest different approaches and describe different stages of asthma to determine the most appropriate treatment.